Paleoenvironment and age of Los Monos Formation (Devonian), Tarija Basin, Argentina and Bolivia (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The objective of this work is to discuss the paleoenvironment and age of the Los Monos Formation, in outcrop and subsurface, along a regional transect (west-east) in the southern sector of the Tarija basin. The lithofacies and ichnofacies of the Alarache, Angosto del Pescado and Balapuca outcrops and core-intervals of the Aguas Blancas xp-13, Ramos x-12, Tartagal x-1 and Tonono x-1 boreholes were analyzed. The definition of lithofacies and ichnofacies allowed us to interpret a shallow to outer shelf paleoenvironment (from the offshore-transition, offshore and shelf). Towards the top of the Tonono Formation, the equivalent of the Los Monos Formation in the Chaco-Salteño was defined as a brackish-waters marginal-marine paleoenvironment. The mineralogy of the mentioned sections plus the Vespucio x-1 borehole was analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM), thus the majority elements in clay minerals were also determined from EDAX. Authigenic and detrital clays from SEM-EDAX were recognized. Four clay mineral assemblages were defined (I+Ch; Ch+I; I+K; K+I), where I+K and K+I assemblages characterize the transgressive events within the basin. The palynofacies of the Balapuca, Alarache and Angosto del Pescado outcrops and samples from the Ramos xp-1002, Ramos xp-1011 and Ramos xp-1012 boreholes were defined, the dominance of terrestrial palynomorphs was identified with variable participation of marine palynomorphs, according to a shallow marine paleoenvironment with shoreline shifts. Two transgressive events were recognized during the late Eifelian-early Givetian and the late Givetian-early Frasnian, which are characterized by an increase in marine components and clay assemblages of I+K and K+I. The palynological associations point to a late Eifelian-early to middle Givetian age for the Los Monos Formation in the study area. The analysis of illite crystallinity and expansive layers in the mixed-layer IS indicated advanced diagenesis for the unit, from late mesodiagenesis (Tonono x-1 and Vespucio x-1) to telodiagenesis (Balapuca and Ramos), according to the final stage of oil generation window to gas generation window, respectively. Finally, based on the mineral composition with a predominance of quartz (>70% in average) and low content of clays (100 km2), the unit has some of the attributes to be considered as a potential shale-type unconventional reservoir.